2005
DOI: 10.1007/s10593-005-0249-6
|View full text |Cite
|
Sign up to set email alerts
|

Hydrolysis of 7,7-Substituted Derivatives of 3-tert-Butyl-3,4-dihydro-2H-thiazolo-[3,2-a][1,3,5]triazin-6(7H)-one

Abstract: CO 3 solution occurs in two steps: in the first step, cleavage of the tetrahydrotriazine ring occurs; and in the second step, opening of the perhydrooxazine ring occurs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
5
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 3 publications
1
5
0
Order By: Relevance
“…In previous work [1], we proposed that the isolation of 2a and 3a or of 2b and 3b from the same reaction mixture is a consequence of a unique Dimroth rearrangement involving aminolytic ring opening a the C (2) -S (1) bond and subsequent parallel recyclization of acyclic intermediate A to give the corresponding aminothiazolinone 2 and aminoimidazolinone 3. Aminolysis of 5-benzylidene-pseudothiohydantoin 1 with opening of the C (2) -S (1) bond in the ring is in accord with experimental findings on the alkaline hydrolysis [2], alcoholysis [3], and aminolysis [4] of derivatives of 2-amino-1,3-thiazol-4(5H)-one (pseudothiohydantoin).…”
supporting
confidence: 86%
See 1 more Smart Citation
“…In previous work [1], we proposed that the isolation of 2a and 3a or of 2b and 3b from the same reaction mixture is a consequence of a unique Dimroth rearrangement involving aminolytic ring opening a the C (2) -S (1) bond and subsequent parallel recyclization of acyclic intermediate A to give the corresponding aminothiazolinone 2 and aminoimidazolinone 3. Aminolysis of 5-benzylidene-pseudothiohydantoin 1 with opening of the C (2) -S (1) bond in the ring is in accord with experimental findings on the alkaline hydrolysis [2], alcoholysis [3], and aminolysis [4] of derivatives of 2-amino-1,3-thiazol-4(5H)-one (pseudothiohydantoin).…”
supporting
confidence: 86%
“…Although the formation of compounds 2a,b may occur without opening of the heterocycle, i.e., directly from the compound 1 by means of addition-elimination at the C (2) =N (2) bond [2], the formation of 3a,b is possible only as the result of ring opening and subsequent recyclization. In previous work [1], we proposed that the isolation of 2a and 3a or of 2b and 3b from the same reaction mixture is a consequence of a unique Dimroth rearrangement involving aminolytic ring opening a the C (2) -S (1) bond and subsequent parallel recyclization of acyclic intermediate A to give the corresponding aminothiazolinone 2 and aminoimidazolinone 3.…”
mentioning
confidence: 99%
“…The bis(hydroxymethyl) derivative of pseudothiohydantoin 1a was prepared as the monohydrate by method [1], compounds 1b,c by [16], the spiro[1,3-dioxan-5,5'(4'H)-1',3'-thiazoles] 2a-e by [2], and compound 6 by [17].…”
Section: Methodsmentioning
confidence: 99%
“…The reaction of urea with formaldehyde and amines has been known since the middle of the last century. It has been found that condensation of urea with formaldehyde and primary monoamines result in the formation of 5-R-1,3,5-triazinan-2-ones [2][3][4][5][6][7]. Similar compounds have been prepared by reacting dimethylolurea 2 with amines: the reaction of equimolar amounts of dimethylolurea 2 and ethanolamine afforded 5-(2-hydroxyethyl)-1,3,5-triazinan-2-one [8][9][10], while the reaction of dimethylolurea 2 with ethylenediamine or hexamethylenediamine in a 2 : 1 molar ratio furnished 5,5′-ethane-1,2-diylbis(1,3,5triazinan-2-one) and 5,5′-hexane-1,6-diylbis(1,3,5triazinan-2-one), respectively [9].…”
mentioning
confidence: 99%
“…However, three-component condensations of urea 1 with formaldehyde and propane-1,3-diamine or butane-1,4-diamine have not been studied previously. Also, the reaction of urea with 1,3,7,9,13,15,19,21-octaazapentacyclo[19.3.1.1 3,7 .1 9,13 .1 15,19 ]octacosane 4 has not been studied.…”
mentioning
confidence: 99%